The Influence of Compensation, Motivation, Job Stress and Job Satisfaction on the Performance of Social Service Employees Bima Regency - Deny Kusumayadi; Hermanto Hermanto; Mery Noviyanti; Syati Irawati; Reza Fitriansyah (Cita Konsultindo Research Center, 2024)
This research aims to analyze and describe the influence of compensation, motivation, work stress and job satisfaction on the performance of employees of the Bima Regency Social Service, both partially and simultaneously. This research uses an associative quantitative research design to look for causal relationships between independent and dependent variables. The respondents for this research were 43 employees of the Bima Regency Social Service. The research instrument is a questionnaire developed from each research variable. Data analysis uses multiple linear regression analysis with the help of the SPSS version 25 application. The research results show that employee work compensation is relatively high, as well as high employee work motivation, but there are several aspects that need to be improved. Employee work stress is relatively low, however, several employees experienced work stress during the Covid-19 pandemic. Employee job satisfaction is also high, which has an impact on high performance. Hypothesis testing shows that compensation, motivation, work stress and job satisfaction, both partially and simultaneously, have a significant effect on employee performance. It is hoped that the results of this research can provide special attention to the Bima Regency Social Service to handle employee work stress quickly and accurately. Apart from that, improving employee performance also requires attention to compensation, motivation and job satisfaction. Future researchers are expected to be able to conduct a more in-depth study regarding the appropriateness of the compensation received by employees compared to prices which continue to experience inflation from year to year, which is not commensurate with the increase in compensation received by employees, thus causing low motivation and high work stress due to the pressure of high demands. and low employee job satisfaction.